2020
DOI: 10.7759/cureus.11315
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Xylitol Plus Grapefruit Seed Extract Nasal Spray Solution in COVID-19: Case Series

Abstract: The SARS-CoV-2 virus has created an unprecedented impact on healthcare globally. Being a novel virus, several treatments have been explored against COVID-19. During the early stages of the disease, treatment is mainly supportive. While several studies have suggested different treatment modalities, there is still no definitive treatment against COVID-19. Re-purposing already established medications, with excellent safety profiles, is a possible approach for treating the disease in its early stage. Having a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…GSE showed anti-viral activity against enveloped viruses, but not against non-enveloped viruses 208. A study by Go et al showed that GSE plus xylitol as a nasal spray solution, commercially available as Xlear nasal spray, can be used as a potential adjunct treatment of COVID-19 209. In silico analysis showed that several components of grapefruit seed extract, including naringenin, bind with Mpro with a binding affinity of −8.2 kcal/mol 195.…”
mentioning
confidence: 99%
“…GSE showed anti-viral activity against enveloped viruses, but not against non-enveloped viruses 208. A study by Go et al showed that GSE plus xylitol as a nasal spray solution, commercially available as Xlear nasal spray, can be used as a potential adjunct treatment of COVID-19 209. In silico analysis showed that several components of grapefruit seed extract, including naringenin, bind with Mpro with a binding affinity of −8.2 kcal/mol 195.…”
mentioning
confidence: 99%
“…There are also other nasal spray formulations for COVID‐19 management and therapeutics that are either before clinical trials or do not have a COVID‐19 (S) protein. These include (1) Xlear nasal spray that contains grapefruit seed extract (GSE) to kill SARS‐CoV‐2 virus and xylitol as a virus decoy, 31 (2) a composite‐based spray that contains algae‐isolated carrageenan and a gellan polysaccharide studied at the University of Birmingham, 32 and (3) an aerosolized formulation termed AeroNabs that contains engineered nanobodies similar to those in llamas and camels to impede spike–ACE2 interactions. 33 …”
Section: Nasal Spray Development For Covid‐19 Managementmentioning
confidence: 99%
“…A newly published case-report series [107] presented three patients with minimalto-moderate risk for morbidity and mortality from COVID-19. The study demonstrated improvement in the symptoms and reduction in the clinical outcome after the use of xylitol and GSE in the form of Xlear nasal spray TM , as an adjunct to their ongoing treatment.…”
Section: Xlear Nasal Spray Tmmentioning
confidence: 99%